2006
DOI: 10.1002/art.21945
|View full text |Cite
|
Sign up to set email alerts
|

Impaired salivary gland function in NOD mice: Association with changes in cytokine profile but not with histopathologic changes in the salivary gland

Abstract: Objective. To characterize the chronologic disease course and possible interrelationships between salivary gland inflammation, hyposalivation, and cytokine levels in NOD mice, a model for Sjögren's syndrome (SS).Methods. NOD mice of different ages were used to mimic different disease stages of SS. Histopathologic findings and rates of salivary secretion were compared between 8-week-old, 17-week-old, and 24-week-old female mice. In addition, 10 cytokines were analyzed in serum and saliva obtained from NOD and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 14 publications
5
92
1
Order By: Relevance
“…Histopathologically, the autoimmune inflammation in the secretory glands of NOD mice accelerates acinar cell loss via apoptosis and necrosis and ductal epithelial hyperplasia by local production of cytotoxic auto-and paracrine factors [16,26]. It is characterized by glandular infiltration by T cells and B cells, primarily in periductal and perivascular areas [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Histopathologically, the autoimmune inflammation in the secretory glands of NOD mice accelerates acinar cell loss via apoptosis and necrosis and ductal epithelial hyperplasia by local production of cytotoxic auto-and paracrine factors [16,26]. It is characterized by glandular infiltration by T cells and B cells, primarily in periductal and perivascular areas [12].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the NOD mouse is the most accurate model, because development of adenitis is accompanied by decreased secretory function in the lacrimal and salivary glands [11]. Lymphocytic infiltration of the exocrine glands of the NOD mouse occurs well before the onset of clinical findings [12]. Although the NOD mouse can also be used as a model for spontaneous type 1 diabetes, the NOD.B10.H2 b strain develops Sjögren's syndrome-like disease, but not diabetes [13].…”
Section: Introductionmentioning
confidence: 99%
“…This morphologic disruption precipitates inflammation with subsequent lymphocytic foci initially consisting of T cells, followed by B cell recruitment. The onset of disease, defined principally by hyposalivation, is then mediated by the combination of acinar destruction, Abs, and proinflammatory cytokines, likely produced by invading lymphocytes (3,6,34,41,43). Conversely, it has been proposed that reduced salivary secretion occurs independently of sialadenitis, but inflammation, once established, exacerbates salivary gland dysfunction (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that NOD mice older than 140 d, subsequent to sialadenitis, have a significant reduction in their capacity to produce saliva on stimulation (39)(40)(41). To determine whether the reduction of sialadenitis can ameliorate salivary gland dysfunction observed in NOD mice, we compared saliva flow rate between NOD, NOD.NZW-Chr7, and NZW mice.…”
Section: Severity Of Sialadenitis But Not Insulitis Is Reduced In Nmentioning
confidence: 99%
“…It spontaneously manifests SS-like histopathologic features and hyposalivation, following a specific time course for the onset of the different SS-related disease manifestations (24). Although some genetic loci related to diabetes have been found to contribute to inflammatory changes in the exocrine glands, diabetes and SS-like disease can develop independently of each other (25).…”
mentioning
confidence: 99%